2016
DOI: 10.1016/j.jpsychores.2016.03.126
|View full text |Cite
|
Sign up to set email alerts
|

Black-white disparities in the association between posttraumatic stress disorder and chronic illness

Abstract: Objective Non-Latino blacks experience a higher proportion of chronic illness and associated disabilities than non-Latino whites. Posttraumatic stress disorder (PTSD) is associated with a greater risk of chronic illness, although few studies have investigated whether the interaction of PTSD with racial disparities may lead to a greater risk of chronic illness among blacks with PTSD than among whites with PTSD. Methods We evaluated data from the population-based National Survey of American Life and the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…It is interesting to note that adolescent intermittent ethanol exposure in rats produces anxiety-like behaviors during immediate withdrawal, a phenomenon that persists into adulthood (Sakharkar et al, 2014 , 2016 ; Pandey et al, 2015 ). However, in adult rats chronic ethanol exposure also produces anxiety-like behaviors, but these behaviors disappear within a few days of last ethanol exposure (Pandey et al, 1999a ; Zhang et al, 2007 ; Aujla et al, 2013 ).…”
Section: Behavioral Effects Of Adolescent Ethanol Exposure Persist Tomentioning
confidence: 99%
“…It is interesting to note that adolescent intermittent ethanol exposure in rats produces anxiety-like behaviors during immediate withdrawal, a phenomenon that persists into adulthood (Sakharkar et al, 2014 , 2016 ; Pandey et al, 2015 ). However, in adult rats chronic ethanol exposure also produces anxiety-like behaviors, but these behaviors disappear within a few days of last ethanol exposure (Pandey et al, 1999a ; Zhang et al, 2007 ; Aujla et al, 2013 ).…”
Section: Behavioral Effects Of Adolescent Ethanol Exposure Persist Tomentioning
confidence: 99%
“…8 Nobles and colleagues found the association between lifetime history of trauma and diabetes to be higher among Blacks compared to Whites. 9 Blacks and Whites with better physical health have higher levels of happiness. 10 However, Blacks and Whites may differ in the association between the two.…”
Section: Introductionmentioning
confidence: 99%
“…The posttraumatic stress disorder checklist was included to capture the influence of trauma on the study population, which has been shown to be associated with an increased likelihood of cardiovascular events [ 33 ], with a disproportionate effect on African Americans [ 34 ]. The research team also included the MoodZoom survey from the original Automated Monitoring of Severity of Symptoms app and Mood Swipe , a 5-point Likert emoticon-based scale of frowny and smiley faces ( ).…”
Section: Methodsmentioning
confidence: 99%